Internationalisation and moral economies in healthcare: NHS exporting and the English patient - Benjamin M. Hunter (Globalization and Health)
Abstract Background Contemporary conditions require detailed study of internationalisation. This article offers a novel perspective on processes of internationalisation in healthcare, adapting an approach from higher education studies and enhancing it with insights from sociological scholarship on moral economies. The article asks how institutions and individuals respond to the globalising healthcare environment, and what this reveals about normative questions that govern healthcare provisioning in national contexts. This is pursued using qualitative data from a study on international commercial services in the English National Health Service (NHS). Results The findings of the research demonstrate how the UK government has sought to build political consensus around specific (commodified) forms of internationalisation in a context of fiscal austerity and xenophobia surrounding the provision of public services. The English NHS has been politically re-imagined as world-leading and of interest as an export industry. Study findings show this stance is premised normatively on processes of subsidy between two apparently distinct spheres – from international (private) to national (public) – but that in practice the distinction is hazy and subsidy at times indirect, routed to individual staff members or to commercial teams. The ascendancy of this as a prevailing, politically legitimate form of internationalisation for the English NHS contrasts sharply with non-commodified alternatives decried as ‘health tourism’. Conclusions The internationalisation framework presented in this article offers a platform for future research that can shed light on the contexts, visions, policies and contestations the emerge as healthcare institutions respond to processes of globalisation. It will be important to avoid uncritical approaches to research and policy by examining not just what forms of internationalisation find favour, and their basis in geographical and racialised hierarchies, but also how approaches to healthcare internationalisation impact inequalities within and between nations.